Translation and cross-cultural adaptation of the Model Disability Survey (MDS) for Brazil - Érika Giovana Carvalho da Silva; Shamyr Sulyvan Castro; Carla Sabariego; Karolinne Souza Monteiro; Núbia Maria Freire Vieira Lima (Universidade de São Paulo, 2023)
ABSTRACT OBJECTIVE This study has as objective the translation and cross-cultural adaptation of the Model Disability Survey (MDS), a World Health Organization instrument that provides comprehensive information on disability/functioning, for Brazil. METHODS This is a cross-sectional methodological study, carried out through five stages - initial translation, synthesis of translations, reverse translation, review by a specialist committee, and pre-test -, considering properties such as semantic, idiomatic, experimental, and conceptual equivalence. Translators, researchers, a mediating team, health professionals, a methodologist and a language specialist were needed to pass through the stages. Statistical analysis was produced from absolute and relative frequencies, measures of central tendency and dispersion, normality tests and content validity index (CVI) > 0.80. RESULTS The MDS has 474 items, which generated 1,896 analyzes of equivalence. Of these, 160 items had a CVI < 0.80 in at least one of the four types of equivalence and required adjustments. After adaptations and approval by the judges, the pre-final version went on to the pre-test with 30 participants from four regions of the Brazilian Northeast. Regarding this sample, 83.3% are women, single, with an average age of 33.7 years (SD 18.8), self-declared as black or brown, active workers, with technical education and living with three residents. Interviews lasted 123 minutes on average, where 127 health conditions were mentioned, and the most frequent cited were anxiety and back pain. Answers were analyzed and 63 items were cited as needing some adjustment, two of which were submitted for analysis by the committee because they presented a CVI < 0.80. The instrument, guide and presentation cards were adjusted after a new pre-test. CONCLUSIONS The MDS was translated and cross-culturally adapted to Brazilian Portuguese and showed adequate content validity.